(untitled) (Research, Society and Development, 2022)
Fish farming is an activity that contributes a lot to food production worldwide, and nutrition is one of the main tools for these animals to reach their maximum productivity. Food expenses are high, so to minimize this factor, experimental designs are of paramount importance as they help in providing information and statistical data for analysis. Therefore, descriptive statistics has assisted researchers to make decisions and improve future experiments, enabling data analysis using the method of multiple comparisons, which varies for each experiment. Thus, this work aimed to survey the experimental design and the tests of comparisons of means used in fish farming papers focused on the area of ​​nutrition, published in the last 20 years. Data were collected from the review of papers from the collection of periodicals, as well as internet search tools, seeking scientific journals specialized in the subject. A hundred papers were selected and tabulated in the spreadsheet Microsoft Office Excel electronics, in which the planning techniques and descriptive statistics used in each research were quantified; afterward, the analyzes were carried out in the R software. The paper concludes that most of the works in the area of ​​Fish farming in the periods from 2000 to 2020 presented satisfactory experimental planning, but concerning the description of the analysis methodology, some left something to be desired, as they did not contain all the parameters defined as essential, for the tabulation and survey of analyses.